Enhancing Self-Regulated Learning for Secondary School Through Education 4.0 Teaching Module - Peter Yacob Yacob; Vikniswari Vija Kumaran; Sai Mei Ling; Darren Peter (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2023)
Education 4.0 is a learning approach that corresponds with the Fourth Industrial Revolution and focuses on reimagining education in light of cutting-edge technology and technologies. The goal of this research is to find out how secondary school teachers perceive about various aspects of Education 4.0. An essential Education 4.0 model was used to organize the empirical study that yielded a literature-based conclusion. In order to attract secondary school teachers, a snowball sampling method was employed. The data for the study came from a set of in-depth, semi-structured interviews and was analyzed using a content-analysis technique. The objective is to implement the foundations of the Education 4.0 revolution in Malaysia's educational system. According to findings, the primary features of Education 4.0 include: open access; customized education; mental transformation; integration of digital technology into education; seamless learning environments; lifelong learning; exploratory education; transdisciplinary learning; and more. Cooperation-communication skills, technology skills, learning skills, and personal traits were identified as top priorities in Education 4.0. Therefore, t he teachers of the Education 4.0 model need to be well-rounded individuals with expertise in technology, mentorship, continuous education, and personality development.